2018
DOI: 10.3892/ijmm.2018.3712
|View full text |Cite
|
Sign up to set email alerts
|

Artesunate induces apoptosis and autophagy in HCT116 colon cancer cells, and autophagy inhibition enhances the artesunate‑induced apoptosis

Abstract: The present study assessed the antitumor effect of artesunate (ART) in vitro and in vivo, as well as its underlying mechanism of action in HCT116 colon cancer cells. An MTT assay, DAPI staining, flow cytometry, western blotting, immunohistochemistry, transmission electron microscopy and TUNEL assay were performed to study the molecular mechanism underlying the antitumor effects of ART in HCT116 colon cancer cells. ART was observed to inhibit proliferation by inducing the apoptosis of HCT116 cells both in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 37 publications
3
68
0
Order By: Relevance
“…Furthermore, emerging studies have demonstrated a link between autophagy and apoptosis. [39][40][41][42] Atg7, an essential autophagy regulator, plays important roles in disease development and progression. 31,33 In this study, we used ATG7 siRNA and 3-MA to inhibit autophagy and explore the potential role of autophagy in NaB-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, emerging studies have demonstrated a link between autophagy and apoptosis. [39][40][41][42] Atg7, an essential autophagy regulator, plays important roles in disease development and progression. 31,33 In this study, we used ATG7 siRNA and 3-MA to inhibit autophagy and explore the potential role of autophagy in NaB-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Overwhelming evidence has elucidated the intricate relationship between apoptosis and autophagy. 41,42 ATG7 has been reported to be a vital regulator in autophagy. [31][32][33] To confirm the interplay between these biological processes, we used 3-MA (3-methyladenine) and ATG7 siRNA to pharmacologically and genetically block autophagy.…”
Section: Autophagy Promotes Apoptosis Induced By Nabmentioning
confidence: 99%
“…In the presence of an autophagy inhibitor, DHA treatment lead to more cell death. Jiang et al also reported that ART induced apoptosis and inhibited cancer proliferation in HCT116 cells both in vitro and in vivo, while treated cells exhibited the concomitant induction of autophagy. The inhibition of autophagy by hydroxychloroquine significantly enhanced ART‐induced apoptosis as indicated by enhanced levels of cleaved caspase‐3 and poly(ADP) ribose polymerase (PARP) .…”
Section: Artemisinin‐induced Autophagy‐dependent Mechanism In Cancermentioning
confidence: 92%
“…Jiang et al also reported that ART induced apoptosis and inhibited cancer proliferation in HCT116 cells both in vitro and in vivo, while treated cells exhibited the concomitant induction of autophagy. The inhibition of autophagy by hydroxychloroquine significantly enhanced ART‐induced apoptosis as indicated by enhanced levels of cleaved caspase‐3 and poly(ADP) ribose polymerase (PARP) . These findings highlight the putative cytoprotective effect of autophagy in ART‐induced apoptosis and suggest that combination therapy with artemisinin and autophagy inhibitors might constitute an effective therapeutic strategy for cancer.…”
Section: Artemisinin‐induced Autophagy‐dependent Mechanism In Cancermentioning
confidence: 92%
See 1 more Smart Citation